A study on SS- π- regular fuzzy ideals of semi groups - Akram S. Mohammed; Samah H. Asaad (Tikrit Journal of Pure Science)
In this paper,  the notion of SS -π- regular fuzzy ideals of semi groups as a generalization of regular fuzzy  ideal has been introduced and some of their important related properties have been investigated. Characterizations of fuzzy interior ideal , anti fuzzy ideal , anti fuzzy bi-ideal and anti fuzzy generalized –bi -ideal in terms of SS - π- regular fuzzy ideal have also been obtained .